Investor protection and constraints relief - Rêgo, Caio Vieira (2016)
Under financial constraints, firms are kept from following first-best policies. It is in the best interests of the regulators to diminish this inefficiencies as firms play such a important roles in the economy as generating employment and contributing to the GDP. One of the channels through which regulation may interfere with firms funding availability is by protecting investors. This research assesses the relationship between investor protection and firms’ financial constraints. I split some of the most common measures of investor protection among three classes: creditor protection, minority protection and external investor protection. This division is relevant to screen the importance of a given class to alleviate the constraints: constrained firms are likely to share some characteristics that make them more akin to rely on given funding source, for example: firms facing asymmetric information problems are more suitable to debt financing. The cash-flow sensitivity of cash is used as a proxy for financial constraints. I construct cash saving models based on a sample of 27471 firms in 393 industries (3 digit-SIC), from 2001 to 2015. The models are fitted in two groups: for firms more likely to be constrained, and for firms less likely. To classify the firms between this two groups I rely on the Size and Age index, and on switching regressions with unknown separation points. The results points that creditor protection is related to lower cash-flow sensitivities of cash for the constrained firms, while external investor protection are related to more prevalent constraints. Minority protection present a negative interaction with the cash-sensitivity of cash in the panel model (indicating constraints relief) but positive coefficient relative to the switching regression. For the unconstrained batch, however, the results are mixed for the creditor protection measure, while external investor protection always diminish the firms’ propensity to save cash.